A framework for sustainability transition: The case of plant-based diets - Markus Vinnari; Eija Vinnari (Springer Netherlands, 2022)
Societal and technological development during the last century has enabled Western economies to achieve a high standard of living. Yet this profusion of wealth has led to several outcomes that are undesirable and/or unsustainable. There is thus an imperative need for a fundamental and rapid transition towards more sustainable practices. While broad conceptual frameworks for managing sustainability transitions have been suggested in prior literature, these need to be further developed to suit contexts in which the overall vision is arguably clear, such as in the case of consuming animal-originated foodstuffs. In this article we introduce a novel transition management framework that is based upon the dimensions of sustainability. The suggested transition management process includes the identification of objectives and obstacles, the listing of options and their opportunities and threats as well as the evaluation of the outcomes (the Five O’s). We argue that sustainability transition management should be a process in which the identification of the relevant dimensions of sustainability and related objectives forms the foundation for strategic, tactical and operational governance activities. We illustrate the practical applicability of the framework in the case of transition towards plant-based diets.